1997
DOI: 10.1128/aem.63.10.4093-4095.1997
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli in settled-dust and air samples collected in residential environments in Mexico City

Abstract: Escherichia coli, an important indicator of the presence of fecal material, was isolated from indoor and outdoor environments in Mexico City. The heterogeneity of E. coli was represented by 89 serotypes, most of them coming from settled-dust indoor samples; 21% of them presented antibiotic multiresistance. The numbers of plasmids were higher among the antibiotic-resistant strains. The results of this study suggest that intestinal infections produced by environmental strains could be of more epidemiological imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Several studies have found that concentrations of contaminants in settled dust were not well associated with concentrations of airborne biological agents (Buttner and Stetzenbach, 1993;Hines et al, 2003). In residential environments, dust-borne and airborne biological agents may represent different ecological niches (Chew et al, 2003b;Rosas et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that concentrations of contaminants in settled dust were not well associated with concentrations of airborne biological agents (Buttner and Stetzenbach, 1993;Hines et al, 2003). In residential environments, dust-borne and airborne biological agents may represent different ecological niches (Chew et al, 2003b;Rosas et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The prior studies reporting the beneficial results of adding betaine have all been performed in environments other than pig sheds, e.g. home and outdoor environments in Mexico (Rosas et al. 1997) and an activated sludge tank, a farmland and off a roof environment (Marthi and Lighthart 1990).…”
Section: Discussionmentioning
confidence: 99%
“…High numbers of Aeromonas spp., pathogenic Vibrio spp., and fecal coliform bacteria were found in floodwater samples [10,11]. Fecal coliform bacteria and pathogenic bacteria were not isolated during current air sampling, although organisms such as Escherichia coli can be readily detected in dust and air samples in contaminated environments [26][27][28].…”
Section: Biological Analysismentioning
confidence: 95%